The efficacy of therapies for post-stroke depression in aging: An umbrella review - Xie, Jinlu; Geng, Xiwen; Fan, Fangcheng; Fu, Xuyan; He, Shuaibing; Li, Tao (Frontiers in Aging Neuroscience, 2022)
Post-stroke depression (PSD) is a common complication after stroke. PSD is associated with emotional disorders and psychological dependence, which are potential risk factors for stroke recurrence and suicidality. This study aimed to perform an umbrella review of PSD therapies through a comprehensive literature search. A systematic search was systematically searched in the PubMed and Web of Science by 2 independent authors. We examined the Hamilton Depression Scale (HAMD), Activities of daily living (ADL), Neurologic function as efficacy endpoints, and the incidence of adverse events as safety profiles. Nineteen eligible studies including 267 clinical trials were included in this study. The results showed that High-Frequency Repetitive Transcranial Magnetic Stimulation, Acupuncture/EA+conventional treatment, Escitalopram, Modified sini san, Moxibustion, Xiaoyao Formula, Paroxetine, Chinese herbal medicine, Exercise, Citalopram, and Cognitive behavioral therapy appear to be beneficial for HAMD in patients with PSD. High-Frequency Repetitive Transcranial Magnetic Stimulation and Sertraline may have an impact on slowing activities of daily living or neurologic functional decline. In addition, Acupuncture/EA+conventional, Escitalopram, Citalopram, Sertraline, and Fluoxetine show no serious adverse events in PSD patients. Our study demonstrated that 11 treatment methods are effective in improving the condition of PSD patients.